Literasi Ekonomi Digital Pekerja GIg: Tantangan Pendidikan dan Strategi Pengembangan SDM Era Digiital - Dwi Putranti, Honorata Ratnawati; Widayati, Tri; Soegiastuti, Janti (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The rapid transformation toward a digital economy has led to the emergence of the gig economy as a new form of employment relationship. This shift demands the development of new competencies among the workforce, particularly in digital economic literacy, which encompasses the ability to manage flexible income, understand platform-related risks, and optimize digital work opportunities. This study aims to explore the experiences of gig workers in building digital economic competencies and to analyze the challenges faced by educational institutions and human resource development (HRD) programs in preparing an adaptive workforce for this flexible work model. Employing a qualitative phenomenological approach, this study investigates the subjective experiences of gig workers in Indonesia. The findings reveal a significant gap between the digital economic competencies demanded by the new work ecosystem and the preparedness provided by formal education and vocational training systems. Based on these findings, the study recommends the development of HRD strategies centered on digital economic literacy, the adaptation of vocational education curricula, and the design of lifelong learning programs to strengthen workforce resilience in the era of the gig economy.